(untitled) (Research, Society and Development, 2021)
The present work aimed to evaluate the rooting potential of stem and root cuttings in the blackberry crop with the cultivars Tupy and BRS Caingu. To carry out this experiment, woody cuttings and root cuttings of the blackberry mother plants were collected. These cuttings were then taken to the greenhouse and placed in expanded polystyrene trays (72 cells) containing a mixture of the commercial Turfa fértil® substrate and expanded vermiculite in a 2: 1 (v: v) ratio. The treatments consisted of different types of cuttings (stem and root) and two cultivars (’Tupy’ and ’ BRS Cainguá’). The experimental design was completely randomized, being a bifactorial (cultivars X type of cutting) with four replications, containing 10 cuttings each. After 97 days of experiment installation, the following parameters were evaluated: percentage of rooted cuttings (%), percentage of survival (%), number of leaves, leaf area (cm²), shoot length and the largest root (cm), fresh and dry mass, and aerial and root system (g) .The propagation of cv. BRS Cainguá can be performed effectively either by stem or root cut. In the case of cultivar Tupy, it had lower rooting potential when compared to ‘BRS Cainguá’. Root cuttings showed higher results in blackberry rooting.